Properti Subjek Bahasa Tetum Dialek Foho di Desa Nanaet Dubessi, Kabupaten Belu, Provinsi NTT - Buha Aritonang (Kantor Bahasa Provinsi Maluku Utara, 2018)
The behavior of language grammar which is variety and language typology which is different from one to others caused subject determination and definition as continually debatable. The subject as one of grammatical relation still needs to have attention by linguist. The purpose of this study describes the subject properties of Tetum language, Foho dialect in Nanaet Dubessi Village, Belu Regency, East Nusa Tenggara Province. It is described by using argument testing predicted as subejct. The method is distributional method. The results show that the Tetum language, Foho dialect has the subject property that (1) appears canonical structure in the praverbal position, (2) can be inserted adverb and negation between the subject and predicate, (3) can be become a relative subject, ( 4) can be inserted between the subject and predicate, (5) can be reflected, (6) can be risen from direct and indirect object to subject through raising mechanism, (7) can focus the subject with the existence of 'ne' focus affixes 'yang’.